PODCASTING AS A MODERN DA’WAH TOOL FOR CONVEYING SIRAH NABAWIYAH - Nazih, Abdullah Ghulam; Hidayatullah, Hidayatullah; Uyuni, Badrah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The rapid advancement of digital media has revolutionized the methods of delivering Islamic teachings, particularly in the realm of da’wah. Podcasts, as a versatile and accessible digital medium, have become increasingly popular for disseminating religious knowledge. This research explores the development and utilization of podcasts as a means for conveying Sirah Nabawiyah (the biography of Prophet Muhammad) through the